The Sustainability and Socio Economic Resilience in Tilapia Farming: A Farmer-Centered Study from Baturaden - WAHYU YULIANI, TRI; Intan Prabandari, Anandhiya (Program Studi Akuntansi Universitas Islam Lamongan, 2025)
This study examines the sustainability and socio-economic resilience of small-scale tilapia farming in Baturaden, Indonesia. Using Participatory Qualitative Modeling (PQ Modeling) combined with farmer interviews and financial analysis, the research explores how local environmental conditions, household livelihood strategies, and institutional factors interact to influence aquaculture outcomes. Results reveal that Baturaden’s high-quality water resources and family-managed ponds enable cost-effective and sustainable production, with significant net profits and rapid return on investment. Farmers employ adaptive strategies such as polyculture and income diversification to enhance resilience, despite challenges including market fluctuations and limited credit access. The study highlights the importance of integrating traditional knowledge with modern practices and calls for targeted policy support to sustain and scale tilapia farming in the region